First Description of the Auditory Region of a Tremarctinae (Ursidae, Mammalia) Bear: The Case of Arctotherium angustidens - Arnaudo, Maria Eugenia; Soibelzon, Leopoldo Héctor; Bona, Paula; Schubert, Blaine (Journal of Mammalian Evolution)
Here we present the first detailed morphological study of the auditory region of a tremarctine bear, the South American giant short-faced bear Arctotherium angustidens. We compared 19 specimens of A. angustidens with other tremarctines and ursines. Through the use of CT scans, we confirmed the presence of a recesus epitympanicus and an anterior incomplete septum of uncertain homology, not related with the septum bullae nor with the longitudinal septum formed by the ecto- and the entotympanic. A secondary crus formed by the lateral semicircular canal (LSC) with the posterior semicircular canal (PSC) of the inner ear was observed in A. angustidens, A. bonariense, Tremarctos ornatus, Ursus spelaeus, and Ursus arctos. This secondary crus was not previously reported for ursids. We also observed that the intraspecific variation in the auditory region of A. angustidens is related to 1) the position of the foramen postglenoideum, 2) the anterior projection of the bulla tympanica over the foramen lacerum and over the opening of the Eustachian tube (medial process of the bulla tympanica), and 3) the projection of the bulla tympanica over the posterior surface of the processus postglenoideus (tympanic process). In addition to this variation, we also identified the presence of interspecific variation in the external auditory region among Tremarctinae and Ursidae. These differences are related to the size of the processus mastoideus and the processus paraoccipitalis, the position of the foramen postglenoideum, and the presence/absence of contact between the bulla tympanica and the processus paraoccipitalis. Fil: Arnaudo, Maria Eugenia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Soibelzon, Leopoldo Héctor. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas ...